Artificial intelligence in healthcare: possibilities of patent protection - T. N. Erivantseva; Yu. V. Blokhina (Фармакоэкономика)
The article provides an overview of the advantages and issues associated with the use of artificial intelligence (AI) and machine learning (ML) in medicine. Based on the analysis of scientific publications, the leading healthcare areas using AI and ML have been identified. The applied problems that modern technologies allow to solve are described, as well as the goals that can be achieved using such technologies. The legal protection issues of technologies using AI are highlighted. A comparison is given of the key aspects of copyright and patent law, and the advantages of patent law and comprehensive patent protection of technologies for process automation in healthcare are presented. The possibilities of complex patent protection and its strategy in the leading areas of AI use in healthcare are considered on specific examples.